2015
DOI: 10.14260/jemds/2015/782
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity Associated With Ureteral Stenting: Study of 90 Cases

Abstract: The present study was an endeavor to study the incidence of double J stent related morbidity. In this prospective study, 90 patients with various indications for DJ stenting were studied for post-stent complications during the immediate post-operative period and on follow up. Out of total 90 patients 59 were male and 31 were female, mean age of patients was 42.64 years. Most common indication for DJ stenting was ureteric calculus followed by hydronephrosis, pelvi-ureteric junction obstruction and ureteric stri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 8 publications
1
5
1
Order By: Relevance
“…Chahal et al 18 in a similar study observed complication rate as 75.5%, which is higher than in present study. Frequency and dysuria were the most common complications observed, occurring in 36.6% and 35.5% of patients respectively.…”
Section: Complicationscontrasting
confidence: 59%
See 4 more Smart Citations
“…Chahal et al 18 in a similar study observed complication rate as 75.5%, which is higher than in present study. Frequency and dysuria were the most common complications observed, occurring in 36.6% and 35.5% of patients respectively.…”
Section: Complicationscontrasting
confidence: 59%
“…Chahal et al 18 in a similar study observed 7 cases (7.8%) complicated with upward stent migration and 3 cases (3.3%) of severe incrustation.…”
Section: Complicationsmentioning
confidence: 80%
See 3 more Smart Citations